Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) in Goat's Milk Kefir Against Pathogenic Microbes - Wardhani, Cindy Heryanti Kusuma (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The purpose of this study was to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of goat milk kefir. This research was conducted from November to December 2021 at the Laboratory of Animal Products Technology, Faculty of Animal Husbandry, Universitas Brawijaya. The analysis of the results of the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) test results was carried out at the Biomedical Laboratory, University of Muhammadiyah Malang. The method used is a laboratory experimental method using a factorial completely randomized design (CRD) with 2 factors, a storage time and concentration. Treatment length of storage consisted of P0 (long storage day 0), P1 (long storage day 7), P2 (long storage day 14), and P3 (long storage day 21). Concentration treatment consisted of K0 (50% concentration), K1 (25% concentration). K2 (Concentration 12.5%), K3 (Concentration 6.25%), and K4 (Concentration 3.10%). Data were analyzed using analysis of variance (ANOVA), and followed by Duncan's Multiple Range Test (DMRT). The results of the analysis showed that the treatment of storage time and concentration showed a very significant difference (P>0.01) on the average MIC and MBC of goat's milk kefir during storage at refrigerator temperature (0-4°C) in Staphylococcus aureus, Escherichia coli, Salmonella typhi. The MIC of goat's milk kefir against Staphylococcus aureus was 12.5% on Escherichia coli and Salmonella typhi 6.25%. While the MBC of goat's milk kefir against Staphylococcus aureus  is 50%, Escherichia coli is 50% and 25%, and Salmonella typhi is 50%, 25%, and 12.5%.Keywords: Kefir, Goat’s Milk, MIC, MBC, Pathogenic Microbes